Proceso de atención de enfermería en un paciente de 62 años con diagnostico insuficiencia renal crónica no especificada - Ruiz Cevallos, Cindy Stephanie (2018)
Chronic renal failure is an increasingly important health problem, due to the increasing incidence and prevalence in recent years. It is defined as the progressive loss and can become terminal when the renal capacity is reduced to 10%, generally irreversible, of the glomerular filtration rate that is translated into a set of symptoms and signs called uremia and which in its terminal stage is incompatible with life. Taking into account the prevalence between 2.5-11% in adults so we can realize that this population is about 200 times higher than the number of patients in renal replacement therapy. If we define CKD due to the presence of albuminuria, the prevalence increases to 10.5-13%. In people older than 65 years, ERC prevalence has been estimated between 25 and 35%, although it is debated whether this represents part of normal aging. This case study is aimed at patients suffering from CRF (Chronic Renal Insufficiency) applied to a 62-year-old patient whose purpose is to put into practice the knowledge of the nursing care process based on the different theorists and thus achieve a detection early of the so-called risk groups of this disease, which will give us the different guidelines to prevent the risk factors to which they entail, also to participate in a joint way with the patients and relatives by means of the counseling of a good follow-up of treatments and adequate nutrition and even in patients who already have this disease at an advanced stage